2020
DOI: 10.21802/gmj.2020.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Relationship Between Nutritional Status and Handgrip Strength in Hemodialysis Patients

Abstract: In hemodialysis patients, the prevalence of malnutrition is high; a decrease in muscle strength is observed.  The objective of the research was to evaluate the nutritional status of hemodialysis patients and the relationship between the nutritional status and muscle strength. Materials and Methods. Sixty hemodialysis patients (38 males, 22 females) were chosen from among volunteers. Food consumption, biochemical values, anthropometric measurements, body composition, physical activity status, subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…According to the SGA scores of the patients participating in the study, 78.4% were in the well-nourished group and 21.6% were in the moderate malnutrition group. Similarly, in a study conducted by Yilmaz and Rakicioğlu, [23] 73.3% of the patients were well-nourished and 26.7% were moderately malnourished according to SGA. Gencer et al [24] reported that 85.5% of the patients were well-nourished, and 14.5% were moderately malnourished.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…According to the SGA scores of the patients participating in the study, 78.4% were in the well-nourished group and 21.6% were in the moderate malnutrition group. Similarly, in a study conducted by Yilmaz and Rakicioğlu, [23] 73.3% of the patients were well-nourished and 26.7% were moderately malnourished according to SGA. Gencer et al [24] reported that 85.5% of the patients were well-nourished, and 14.5% were moderately malnourished.…”
Section: Discussionmentioning
confidence: 80%
“…In the evaluation of hand grip strength of these patients, reference values of healthy individuals are used. [23] Pekcan and Kılıç, [28] reported the reference hand grip strength values for healthy individuals as 42.3 ± 7.3 kg for the right hand and 41.5 ± 7.3 kg for the left hand in males; 24.7 ± 5.2 kg for the right hand and 23.2 ± 5.0 kg for the left hand in females. In our study, hand grip strength was 19.39 ± 5.70 kg and 12.40 ± 5.58 [17.60 (12.70-35.80); 12.15 (6.00-28.40)] kg for male and female patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation